Community-based analysis of stroke prevention and effect of public interventions in atrial fibrillation: results from the ARENA project - Zylla, Maura Magdalena; Özdemir, Belgin; Hochadel, Matthias; Zeymer, Uwe; Akın, Ibrahim; Grau, Armin J.; Schneider, Steffen; Alonso, Angelika; Waldecker, Bernd; Süselbeck, Tim; Schwacke, Harald; Haass, Markus; et al. (Clinical research in cardiology, 2025)
Community-based interventions may promote awareness and adherence to atrial fibrillation (AF)-related therapies, potentially reducing adverse events. The ARENA project investigated the health status, therapies and events in AF patients in the Rhein-Neckar Region, Germany. The subproject “ARENA intervention” studied the effect of community-based interventions on AF-associated outcomes.
Online veröffentlicht: 08. August 2024
Gesehen am 28.07.2025